Small fiber neuropathy - Natalya A. Suponeva; Natalia V. Belova; Natalia I. Zaitseva; Djamilya G. Yusupova; Dmitry Yu. Lagoda; Olga S. Korepina; Mikhail A. Piradov (Анналы клинической и экспериментальной неврологии, 2017)
Despite the fact that small fiber neuropathy (SFN) has already been studied for 30 years, it remains one of the most mysterious diseases that are extremely difficult to diagnose and cure. The prevalence of SFN is 52.95 per 100,000 population; diabetes mellitus is considered to be the most frequent cause of this disease. Chronic neuropathic pain syndrome, temperature sensation abnormalities, and vegetative disorders develop as a result of damage to fine myelinated А- and unmyelinated C fibers. The disease mainly spreads in the upward direction: from feet to the proximal body parts and arms; primary axonal damage takes place. Although SFN is believed to be one of the most benign neuropathy types as it does not affect the large sensory and motor fibers, it significantly decreases patients quality of life.